2006
DOI: 10.1002/eji.200635937
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for IL‐6 and IL‐12p40 in mediating protection against Leishmania donovani and the expansion of IL‐10+ CD4+ T cells

Abstract: Adoptive dendritic cell (DC) immunotherapy provides a useful experimental tool to evaluate immunoregulation in vivo and has previously been successfully used to enhance host resistance in a variety of experimental models of leishmaniasis. Here, we used this approach to identify IL‐6 and IL‐12p40 as critical cytokines that cooperate to mediate host protection to Leishmania donovani but which act independently to regulate expansion of IL‐10+ CD4+ T cells, shown here for the first time to be associated with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
123
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(155 citation statements)
references
References 48 publications
(59 reference statements)
25
123
3
1
Order By: Relevance
“…In our system, transfer of DC primed with CpG was able to confer protection to IL-6 -/-susceptible mice, indicating that in our vaccine DC are crucial in initiating protective responses after vaccination with Lm + CpG. This finding reinforces what has been recently published by Stager et al in mice infected with L. donovani [42]. These authors found that transfer of BMDDC activated with LPS reduced parasite burden and blocked the expansion of IL-10-secreting CD4 + T cells in the visceral leishmaniasis model.…”
Section: Discussionsupporting
confidence: 90%
“…In our system, transfer of DC primed with CpG was able to confer protection to IL-6 -/-susceptible mice, indicating that in our vaccine DC are crucial in initiating protective responses after vaccination with Lm + CpG. This finding reinforces what has been recently published by Stager et al in mice infected with L. donovani [42]. These authors found that transfer of BMDDC activated with LPS reduced parasite burden and blocked the expansion of IL-10-secreting CD4 + T cells in the visceral leishmaniasis model.…”
Section: Discussionsupporting
confidence: 90%
“…For example, increased expression of interleukin-10 during chronic L. donovani infection 32 may aid in limiting any toxic shock response. 33 On the other hand, although increased local interferon-␥ and tumor necrosis factor-␣ may enhance macrophage bactericidal activity, the threshold of macrophage activation remains below that necessary to achieve anti-leishmanial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ Foxp3 Ϫ cells in L. donovani infection (54). Because BALB/c and IL-4R␣ Ϫ/Ϫ mice have similar parasite loads ( Fig.…”
Section: Cd25mentioning
confidence: 98%